2011
DOI: 10.1007/s00586-011-1788-4
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Korean version of the Roland–Morris Disability Questionnaire

Abstract: We evaluated the reliability and validity of an adapted Korean version of the Roland-Morris Disability Questionnaire (RMDQ). Translation/retranslation of the English version of RMDQ was conducted, and all steps of the cross-cultural adaptation process were performed. The Korean version of the Visual Analog Scale (VAS) measure of pain, RMDQ, and the previously validated Oswestry Disability Index (ODI) were mailed to 100 consecutive patients with chronic lower back pain (LBP) of at least 3 months. Eighty-one pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 18 publications
(23 reference statements)
2
29
0
2
Order By: Relevance
“…The Hungarian RMQ showed excellent correlation with the ODI. The result is in accordance with the correlation of ODI with the earlier published Argentinean (0.81) [29], German (0.80) [30], Japanese (0.78) [31], Korean (0.78, 0.80) [32] and Chinese (0.79) [ The literary recommendation [26] in this case, would be at least 0.70, but the ICC value in the present study turned out to be far more favorable. The ICC results of some other national versions are a bit lower: German (0.82) [30], Norwegian (0.89) [35], Persian (0.86) [36], Spanish (0.87) [37] and Turkish (0.86) [38].…”
Section: Validitysupporting
confidence: 95%
“…The Hungarian RMQ showed excellent correlation with the ODI. The result is in accordance with the correlation of ODI with the earlier published Argentinean (0.81) [29], German (0.80) [30], Japanese (0.78) [31], Korean (0.78, 0.80) [32] and Chinese (0.79) [ The literary recommendation [26] in this case, would be at least 0.70, but the ICC value in the present study turned out to be far more favorable. The ICC results of some other national versions are a bit lower: German (0.82) [30], Norwegian (0.89) [35], Persian (0.86) [36], Spanish (0.87) [37] and Turkish (0.86) [38].…”
Section: Validitysupporting
confidence: 95%
“…26 , 31 , 34 Previous studies also found the RMDQ easy to administer, with few misunderstandings or declining participation, or requiring major adjustments. 11,13,20,26,30,33 The simplifi ed Chinese 31 and Persian 15 versions found missing data for the Oswestry Disability Index (ODI) when compared with the RMDQ particularly in the Sex Life subscale, which the RMDQ does not contain. The ODI was adapted to Tunisian Arabic.…”
Section: Discussionmentioning
confidence: 98%
“…La magnitud de esta correlación entre dolor y discapacidad en nuestro trabajo es menor que la reportada en trabajos previos, como en la validación tunesina 5 , coreana 11 , así como también en el trabajo original de Roland y Morris 14 . A diferencia de estos trabajos, nuestra muestra no estaba constituida por personas con dolor crónico en el momento de la evaluación, lo que puede explicar la menor relación observada entre discapacidad y dolor en nuestros pacientes.…”
Section: Discussionunclassified
“…Estas validaciones han mostrado buenos indicadores psicométricos, por lo que se cuenta con un instrumento adecuado para evaluar discapacidad por dolor lumbar en diferentes países. Citamos por ejemplo la versión alemana 4 , tunesina 5 , española 6 , brasilera 7 , china 8 , gujarati (India) 9 , japonesa 10 y coreana 11 . Sin embargo, carecemos de una versión validada en Chile, que nos permita usar con propiedad este instrumento en nuestro país.…”
unclassified